ESTIMATION OF POLYCYCLIC AROMATIC HYDROCARBONS (PAH’s) PRESENT IN THE ATMOSPHERE OF URBANIZED REGION BADAMI BAGH IN LAHORE, PAKISTAN (Pakistan Journal of Science, 2016)
The emerging mega city of Lahore has been progressing by leaps and bounds in last two decades which is directly related to an immense increase of number of vehicles and power generation systems using fossil fuels. The present study entails the quantification and evaluation of potential risk due to Polycyclic Aromatic Hydrocarbons (PAHs) which is one of the known organic pollutants from vehicular, power generation system’s exhaust and other industrial activities. The samples of Total Suspended Particulate Matters (TSPM) were collected from various urbanized sites present at Badami Bagh, Lahore, Pakistan for the estimation of polycyclic aromatic hydrocarbons. The technique used for quantification of PAH’s was Gas Chromatography. The concentration of mean total of PAH was 746.60 ng/m3. Dibenzo(a,h) Anthracene was found to be in highest concentration of 142.35 ng/m3 among all the polycyclic aromatic hydrocarbons under investigation.
Keywords: Polycyclic Aromatic Hydrocarbon (PAHs); Total Suspended Particulate Matter (TSPMs); Gas Chromatography; Organic Pollutant